A GENDER PERSPECTIVE IN MITIGATING FALL ARMYWORM (Spodoptera frugiperda) TOWARDS ENVIRONMENTAL AND FOOD PRODUCTION RESILIENCE IN BOMET COUNTY, KENYA: Effects of Fall Armyworm invasion on Food Production between Differentiated Headed Households in Bomet County, Kenya - Nyakwara, Zilpher (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2023)
The emergence and rapid spread of the fall armyworm (FAW) Spodoptera frugiperda in Africa having spread from its Native American since 2016 seriously threatens the food crop production of millions of smallholder farmers. In December 2016, the Kenyan government started experiencing the invasion of FAW threatening the food crop production in the country. Smallholder farmers have different household setups with gender differentials towards managements of any new invasive crop pests including FAW. From literature reviews, fall armyworm invasion can affect food production to zero production if not properly managed but there are gaps on effects of fall armyworm within different headed households by gender prompting the study on effects of fall armyworm invasion on food production between differentiated headed households in Bomet County, Kenya. Data was collected using multiple approaches including interviews on households and key informants, focus group discussions and observations. A household baseline survey and focus group discussions were done using a structured questionnaire and checklist where a total of 384 respondents were enumerated. The study result showed that the management of fall armyworm are gender specific with different gender roles and activities being used. Therefore, gender specific programs and different headed households should be approached differently during agricultural production using an effective network of extension and advisory which provides technical advice on management of new invasive pests towards food production and environmental resilience